Evidence of spin-density-wave to spin-glass transformation in YNd alloys - Trovarelli, O.; Sereni, J.G.; Pureur, P.; Shaf, J.; Sereni, Julián (American Physical Society, 1995)
Fil: Trovarelli, O. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina